2017
DOI: 10.1016/j.molcel.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Generation and Loading of DNA Guides by Bacterial Argonaute

Abstract: Several prokaryotic Argonaute proteins (pAgos) utilize small DNA guides to mediate host defense by targeting invading DNA complementary to the DNA guide. It is unknown how these DNA guides are being generated and loaded onto pAgo. Here, we demonstrate that guide-free Argonaute from Thermus thermophilus (TtAgo) can degrade double-stranded DNA (dsDNA), thereby generating small dsDNA fragments that subsequently are loaded onto TtAgo. Combining single-molecule fluorescence, molecular dynamic simulations, and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
178
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(195 citation statements)
references
References 47 publications
12
178
0
2
Order By: Relevance
“…Similar to previously published structures of RsAgo (Miyoshi et al, 2016) and TtAgo (Sheng et al, 2014; Swarts et al, 2014a, 2017; Wang et al, 2009), the 5′-phosphate of the guide strand is positioned within the MID pocket and anchored in place through a network of direct hydrogen bonds from amino acid side chains originating from the MID (Tyr463, Lys467, Gln478, and Lys506) domain (Figures 3A and 3B). Indeed, mutation of Tyr463 and Lys467 residues make RsAgo unable to bind RNA guides in vivo (Olovnikov et al, 2013) and in vitro (Miyoshi et al, 2016).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar to previously published structures of RsAgo (Miyoshi et al, 2016) and TtAgo (Sheng et al, 2014; Swarts et al, 2014a, 2017; Wang et al, 2009), the 5′-phosphate of the guide strand is positioned within the MID pocket and anchored in place through a network of direct hydrogen bonds from amino acid side chains originating from the MID (Tyr463, Lys467, Gln478, and Lys506) domain (Figures 3A and 3B). Indeed, mutation of Tyr463 and Lys467 residues make RsAgo unable to bind RNA guides in vivo (Olovnikov et al, 2013) and in vitro (Miyoshi et al, 2016).…”
Section: Resultssupporting
confidence: 79%
“…Similarly, sequence-specific recognition of the 5′-base in the guide strand were shown for several eukaryotic Agos (Boland et al, 2010; Frank et al, 2010; Matsumoto et al, 2016; Schirle and MacRae, 2012; Wang et al, 2009; Mi et al, 2008). On the contrary, TtAgo was proposed to have little specificity for the 5′-base binding (Swarts et al, 2014a, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-crRNA is cleaved within the repeat region, which adopts a pseudoknot structure (Swarts et al, 2017; Yamano et al, 2016). In the structure of Cas12a bound to a pre-crRNA, the scissile phosphate is directly positioned between the sidechains of highly-conserved histidine and lysine residues within the WED domain (Swarts et al, 2017).…”
Section: Type V Crispr-cas Systemsmentioning
confidence: 99%
“…The pre-crRNA is cleaved within the repeat region, which adopts a pseudoknot structure (Swarts et al, 2017; Yamano et al, 2016). In the structure of Cas12a bound to a pre-crRNA, the scissile phosphate is directly positioned between the sidechains of highly-conserved histidine and lysine residues within the WED domain (Swarts et al, 2017). Although early studies suggested that pre-crRNA cleavage requires divalent metal ions (Fonfara et al, 2016), subsequent studies showed that Mg 2+ ions help stabilize Cas12a binding to the RNA but are not required for catalysis (Swarts et al, 2017).…”
Section: Type V Crispr-cas Systemsmentioning
confidence: 99%